Tools and Biomechanical Modeling Use in Legal Disputes: Some Case Studies - Durante, Francesco (Frontiers in Bioengineering and Biotechnology, 2019)
The paper presents some of the biomechanical tools available for the forensic bioengineering expert. The tools range from the simple three-dimensional modeling environment to represent the geometries up to the analytical models based on the free-body diagram and the multibody numerical models of rigid bodies. Through these tools the forensic bioengineering expert is able to solve complex problems by providing quantitative results based on a scientific approach. In this work three case studies, representing real cases that were treated in court, are presented. They relate to accidents which occurred in different contexts. The first relates to an accident in a filament factory where a worker remained with her body stuck in the production line, the second the hit of a pedestrian, and the last concerning a worker who fell from a wall on a construction site. It is shown that the approach to modeling may not always be necessarily complex. It was possible to solve the first case with a simple three-dimensional geometric model that clearly highlighted the development of the facts. In the second case it was possible to set up a simple analytical model based on a free body diagram to search for the relationship between the forces developed on the invested leg, demonstrating the relationship between the accident and the injuries reported. The third case, with the need for more complex modeling, was instead treated with a kinematic and dynamic multibody model which allowed the dynamics of the accident to be traced, starting from the final position in which the victim was found. In each case, the competence of the forensic bioengineering expert was crucial in identifying the correct modeling for the case in question, with the choice of the right data, in order to arrive at reliable quantitative results.